Synthesis, crystal structure and electronic applications of monocarboxylic acid substituted phthalonitrile derivatives combined with DFT studies - Tunc, Gulenay; Canmkurbey, Betul; Dedeoglu, Burcu; Zorlu, Yunus; Eryilmaz, Serpil; Gürek, Ayşe Gül (Elsevier, 2021)
Monocarboxylic acid substituted phthalonitrile derivatives (PN1 and PN2) have been synthesized and their molecular geometries and hydrogen bond interactions investigated with single cystal X-ray diffraction analysis. PN1-a and PN2 crystal structures linked by a pair of O-H center dot center dot center dot O hydrogen bonds form classical carboxylic acid inversion dimers, whilst PN1-b crystal structure stabilized by classical O-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonding interactions. Spectral characterizations of PN1-a and PN2 structures have been performed by FT-IR, H-1-C-13 NMR and UV-Vis techniques. Molecular structure optimization and structural properties of PN1 and PN2 in the forms of monomer and dimer have been studied with the DFT approach, B3LYP functional and 6-311++G(d,p) basis set. The effects of dimeric forms of structures on geometrical and spectral parameters have been evaluated together with the values of monomeric forms and experimental ones. Concepts specific to electronic absorption spectra such as absorption wavelengths and major contributions to electronic transitions and FMOs energy values have been determined by TDDFT approach. Some reactivity properties of the monomer PN1-a and PN2 structures have been evaluated through global, local parameter values and MEP visuals. It was shown that PN2 monomer structure which has both a low HOMO-LUMO energy gap (Delta E=3.83 eV(-1)) and a higher chemical softness value (S=0.52 eV(-1)) is more reactive than PN1-a monomer. The potentials of being nonlinear optical (NLO) material and some thermodynamic parameters that are thought to contribute to their structural properties have been determined theoretically for PN1-a and PN2 monomeric forms. Furthermore, it is determined that PN2 has superior properties compared to PN1 based on the electrical characterization of the compounds. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Phthalonitrile; Carboxylic acid; Spectral analysis; DFT; Monomer and dimer; Conductivity